Commodification of humanitarian sentiments in celebrity endorsements: a case study of Africa - Shahinaz Hesham El Samadoni; Monika Jiménez-Morales (Insights into Language, Culture and Communication, 2022)
The relationship between humanitarian campaigns and celebrity industry is complex and debatable. The pervasiveness of celebrity led campaigns has recently become a prominent issue in the non-profit sector. Celebrities are increasingly viewed as powerful actors in international politics, particularly in altering North-South relations. Celebrities’ great exposure and various humanitarian initiatives have become widely discussed subjects in popular media. The current study is concerned with the mediation of distant Others who are suffering in Africa, and how Western celebrity endorsement through humanitarian sentiments influences this mediation experience. Within this framework, the concept of “mediation” is a coined process. First, by overcoming the distance in communication between the distant Others and the spectators, or in other words between those in front of and those behind media screens. Second, by passing through the medium. The study relies on a qualitative method approach of detailed content analysis. Appraisal framework has been used in the current study to analyze the verbal/visual resources of the feature humanitarian articles of the 15 selected celebrities. In this respect, a total of 51 headlines, 28 leads and body paragraphs and 30 images have been analyzed. The analysis uncovers how the articles depict the efforts of the Western celebrities along with shaping the image of the sufferers. It is found that the celebrities are evaluated positively, while the sufferers and Africa are evaluated negatively on the verbal and visual levels.